Ten Years of Gdp Evolution in Correlation with the Turnover. The Case of Romania - Olga Plesco; Neculai Tabara (CES Working Papers, 2012)
The economic environment must be parsed because of the multitude of phenomena that determine developments which generate effects and show sinuous ridges that can be interpreted differed depending on the context. Tourism is an important sector of the economy, and the evolution must be analyzed through the signification of a set of specific indicators. However, there are common indicators for all the areas of activity which are relevant both for industry and for the country's economic level. Thus, the analysis of the achieved turnover by the most successful travel agencies in conjunction with the evolution of gross domestic product per capita is important and highlights significant elements for the future forecasts, and analysis of the business environment in this area. The time period under analysis should be long enough so that the valuable judgments are issued from the normal not random trend of the indicators.
Keywords: C82; D39; E01; 330; GDP; turnover; tourism; analysis Romania